Measuring Energy Security – A Conceptual Note - Manuel Frondel; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Along with the oil price, concerns about the security of energy supply have soared once again in recent years. Yet, more than 30 years after the OPEC oil embargo in 1973, energy security still remains a diffuse concept. This paper conceives a statistical indicator that aims at characterizing the energy supply risk of nations that are heavily dependent on energy imports. Our indicator condenses the bulk of empirical information on the imports of fossil fuels originating from a multitude of export countries as well as data on the indigenous contribution to the domestic energy supply into a single parameter. Applying the proposed concept to empirical energy data on Germany and the U.S. (1980-2004), we find that there is an inter-temporally increasing gap in the energy supply risk between both countries, with Germany suffering much more from a tensed energy supply situation today than the U.S.
Keywords: C43; Q41; 330; Herfindahl index; energy supply risk indicator; Energieversorgung; Fossiler Energieträger; Import; Marktanteil; Konzentrationsindex; Deutschland; USA